2022
DOI: 10.1186/s12951-022-01270-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of post-surgery tumour recurrence via a sprayable chemo-immunotherapy gel releasing PD-L1 antibody and platelet-derived small EVs

Abstract: Background Melanoma is the most serious type of skin cancer, and surgery is an effective method to treat melanoma. Unfortunately, local residual micro-infiltrated tumour cells and systemic circulating tumour cells (CTCs) are significant causes of treatment failure, leading to tumour recurrence and metastasis. Methods Small EVs were isolated from platelets by differential centrifugation, and doxorubicin-loaded small EVs (PexD) was prepared by mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Apart from mimicking platelet and modulating platelet functions, the applications of platelet derivatives have received increasing attention in recent years. For example, small extracellular vesicles released by activated platelets can participate in some specific physiological and pathological processes. Furthermore, platelet-derived polyphosphates can be used as procoagulants to control hemorrhage. In this section, the potential nanotherapeutics driven by platelet derivatives will be discussed, including mainly two aspects: (i) platelet extracellular vesicle-derived nanotherapeutics and (ii) platelet polyphosphate-based nanotherapeutics.…”
Section: Platelet Derivative-based Nanotherapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from mimicking platelet and modulating platelet functions, the applications of platelet derivatives have received increasing attention in recent years. For example, small extracellular vesicles released by activated platelets can participate in some specific physiological and pathological processes. Furthermore, platelet-derived polyphosphates can be used as procoagulants to control hemorrhage. In this section, the potential nanotherapeutics driven by platelet derivatives will be discussed, including mainly two aspects: (i) platelet extracellular vesicle-derived nanotherapeutics and (ii) platelet polyphosphate-based nanotherapeutics.…”
Section: Platelet Derivative-based Nanotherapeuticsmentioning
confidence: 99%
“…Moreover, platelet-derived EVs might reduce TNF-α and IL-8 production, thereby suppressing inflammation . Due to their unique features, various functions and ease of clinical translation, platelet EVs as nanocarriers loaded with functional cargoes hold considerable promise mainly for (i) cancer cell adhesion and (ii) inflammation regulation. …”
Section: Platelet Derivative-based Nanotherapeuticsmentioning
confidence: 99%
“…Immunotherapy combined with chemotherapy is considered a reliable treatment option, but improving its bioavailability and targeting is the key to achieving efficient treatment [ 251 , 252 ]. Sun et al [ 253 ] proposed a dual-lumen nano hydrogel spray to inhibit postoperative tumor recurrence and metastasis by reviving the body's immune system. Tube A has fibrin and α-PD-L1, and tube B is thrombin and PexD, a platelet-derived extracellular vesicle (Pex) loaded with DOX.…”
Section: Hydrogel Nanomaterialsmentioning
confidence: 99%
“…5). 156 It was observed that PexD activity could improve the combination with tumor cells, prompt further immunogenic tumor cell death and stimulate a more intense anti-tumor immune response compared with DOX solution. Furthermore, the sprayable immunotherapeutic fibrin gel could activate the host's innate immune system, thus inhibiting the potential of local melanoma recurrence and metastasis post-surgery.…”
Section: Applications Of Sprayable Hydrogelsmentioning
confidence: 99%